Relações parentais e a prevenção ao uso de drogas: contribuição piagetiana - Freiria, Marcos Henriques da [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
In this dissertation, we present the results of a Master's Degree in Education which objective was to verify the influence of the parental educational style in the prevention of psychoactive substances use by adolescents. Also, it was investigated whether there was an association between the type of respect (unilateral and mutual) and prevention of drug use, based on the moral psychology of Jean Piaget. The case study was developed in a public school located in the periphery of a medium-sized city of the western region of São Paulo. The subjects were 33 students of both sexes, enrolled in the 9th year of elementary education, aged between 13 and 17 years and socioeconomic level C, according to criteria defined by the Brazilian Association of Research Companies. Through a questionnaire and interviews based on the Piagetian Clinical Method, it was possible to verify that there isn’t a relationship between parental educational styles and use of psychoactive substances. However, there seems to be such relation regarding to the nature of the drugs consumed, because the subjects who were submitted to the authoritative style made use of the lawful ones. It was possible to verify the prevalence of unilateral respect between parents and children and the existence of a relationship between use of psychoactive substances, gender, family structure, religious practice and level of information about drugs. Considering these aspects, the conclusion is that the work regarding the prevention of drug use should consider the kind of respect established between parents and children.

Nesta dissertação, apresentam-se resultados de pesquisa de mestrado em Educação cujo objetivo, entre outros, foi o de verificar a influência do estilo educativo parental na prevenção ao uso de substâncias psicoativas pelos adolescentes. Paralelamente, investigou-se também se havia associação entre o tipo de respeito (unilateral e mútuo) e a prevenção ao uso de drogas, tendo como parâmetro a psicologia moral de Jean Piaget. Tratou-se de um estudo de caso, desenvolvido numa escola pública localizada na periferia de uma cidade de médio porte da região oeste paulistana. Os sujeitos foram 33 estudantes matriculados no 9º ano do Ensino Fundamental II, de ambos os sexos, com idade entre 13 e 17 anos e nível sócio econômico C, segundo critérios definidos pela Associação Brasileira de Empresas de Pesquisa. Mediante questionário e entrevistas baseadas no método clínico piagetiano, constatou-se que não há associação entre estilos educativos parentais e uso de substâncias psicoativas. Contudo, parece existir tal relação no tocante à natureza das drogas ingeridas, pois os sujeitos que foram submetidos ao estilo autoritativo só fizeram uso das lícitas. Verificou-se, ainda, o predomínio do respeito unilateral entre pais e filhos e a existência de relação entre uso de substâncias psicoativas, gênero, estrutura familiar, prática religiosa e nível de informação sobre as drogas. Concluiu-se, além de outros aspectos, que os trabalhos de prevenção ao uso de drogas devem contemplar o tipo de respeito estabelecido entre pais e filhos.
Parental relationships and drug abuse prevention: according to piagetian contribution
Keywords: Adolescentes; Drogas; Relação parental; Psicologia moral; Jean Piaget